The dynamics in requested and granted loan terms when bank and borrower interact repeatedly - Karolin Kirschenmann (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
This paper studies how credit constraints develop over bank relationships. I analyze a unique dataset of matched loan application and loan contract information and measure credit constraints as the ratio of requested to granted loan amounts. I find that the most important determinants of receiving smaller than requested loan amounts are firm age and size at the time of the first interaction between borrower and bank. Over loan sequences, credit constraints decease most pronouncedly in the beginning of relationships and for the initially young and small firms. Moreover, the structure of the dataset allows me to disentangle the demand and supply effects behind these observed credit constraints. I find that the gap between requested and granted loan amounts decreases because both sides converge. If previous credit constraints were large, requested amounts increase more moderately, while granted amounts increase more strongly than in the case of small previous constraints. The findings are a sign of the use of dynamic incentives at the bank side to overcome information problems when contracting repeatedly with opaque borrowers. The results further suggest that, particularly in the beginning of a bank relationship, borrowers learn from their previous experience with credit constraints and adjust their demand accordingly.
Keywords: D82; G20; G21; G30; 330; Relationship lending; credit constraints; small business lending; asymmetric information; learning